A STUDY ON EDIBLE CUTLERY AND ITS SIGNIFICANCE ON THE INDIAN HABITAT WITH SPECIAL REFERENCE TO RESTAURANTS IN MUMBAI (International Journal of Food and Nutritional Sciences, 2022)
Plastic and wood are the two materials that have been globally known for their involvement in all walks of life. One such area being single use cutlery has had adverse environmental, social and physiological impact due to these two materials being actively used. Plastic and wood cutlery can alter habitats and natural processes, reducing ecosystems' ability to adapt to climate change and affecting the livelihoods, and social well-being of millions of people. “Edible - Cutlery” are the two words that can be the future of our world, the change to our environment and an innovative approach to eliminate the use of other single-use cutlery available in the market. The concept of edible-cutlery is one of the finest approaches that blink out global issues like solid-waste management, wastage of groundwater, and environmental degradation. Despite immense popularity and universal adoption, very little is known about promoting edible cutlery. The Studies conducted in the past only focus on certain components rather than the problem, causes and solutions as a whole. The purpose of this study was to highlight the negative impact of using plastic and wooden cutlery and the impending problem of wastage of groundwater for the production of large-scale paddy crops, which can be resolved through edible cutlery. Statistical test is used to hypothesize the relationship of variables. The methodology used in the research were aimed at two target audiences namely consumers and restaurants through the help of a structured form questionnaire which received 134 responses from consumers and 10 responses from restaurants. The finding demonstrates that both the target audiences had contrasting views on the adoption of edible cutlery. Outcome of the research paper helps to encourage the mass adoption of edible cutlery, and motivates businesses to adopt edible cutlery in their practices and contribute towards a greener society whereas consumers will be drawn to tilt towards a healthier alternative.